The Book of Ruins and Desire: Interactive Mechatronic Sculpture - Jennings, Pamela L. (Sisters in the Life: A History of Out African American Lesbian Media-Making, 2018)
The interactive book is a term heard frequently in reference to early experiments in multimedia production. But how to translate the concept of the book into a medium that has no paper, no pages, remains a challenge. Is not a book an object one holds in one’s hands—the cover affected over time by the acids and oils perspiring from the user’s skin, pages turned down and yellowed, torn or marked up? Research could show that the notion of the traditional book has been challenged throughout history. But this challenge has been accelerated with the growing accessibility of new computer
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Créateur.rice LGBTQ+; 5-Créateur.rice noir.e; _Nettoyé